(3QSGdI aj GdehSjbis - (3eMeO SfGQs ((3eMehO UObi s)
(3ChdgG (B:s
(3hHYO adeG cGf Yde GdehSjbi ef CTQa GdYdhe GdQjGVjI s
(3BNQgG (B:s
(3aCUd GdCfZGe ef Pdc GdWGFQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ehSjbi JjehQ (B15) s
Keywords: (3GdehSjbi hGdZfGAs